Armenian Culture from the Semiotic Perspective - Matevosyan, Armine; Dalalyan, Manana (Armenian Folia Anglistika, 2016)
The present paper goes along the lines of Semiotics, a branch of linguistics. It studies the system of signs which takes the form of words, images, sounds, gestures and objects. Through the usage of signs we represent the linguocultural aspect of our knowledge, ethnic traditions and folklore. The interest we take in the paper is the study of signs and symbols in Armenian culture. Culture, including miniature paining, singing, dancing, architecture and cuisine, may involve any sphere of Armenian identity. Signs and symbols that constitute language and culture are constructed through verbal and non-verbal interactions and are arbitrary. The purpose of our analysis is to specify what why, whom questions in a specific context of situation, as well as in a large context of culture, such as social community, media and communication.